(untitled) (Perioperaciina Medicina, 2022)
Sedation is an important aspect of adequate treatment of patients in the intensive care unit. Recent drug developments and new ventilation strategies provide improved sedation management that allows for better adaptation to the clinical condition and individual needs of the patient. This article provides an overview of the general principles of sedation of patients in intensive care units and focuses on a relatively new drug in the pharmaceutical market of Ukraine — dexmedetomidine. Given the pandemic of coronavirus disease COVID-19, there was carried out a review of the international and domestic literature describing the use of dexmedetomidine as a sedative and analgesic in patients with acute respiratory distress syndrome caused by SARS-COV-2 virus. Its anti-inflammatory and antioxidant properties are also described, which will allow the use of the drug in complex therapy in the treatment of COVID-19 in severe patients.